2017
DOI: 10.1111/acer.13422
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol During Adolescence Impacts Corticolimbic Dendritic Spines and Behavior

Abstract: Background Risk for alcohol use disorders (AUDs) is linked to alcohol drinking during adolescence, but understanding of the neural and behavioral consequences of alcohol exposure during adolescence remains incomplete. Here, we examined the neurobehavioral impact of adolescent chronic intermittent EtOH (CIE) vapor exposure in mice. Methods C57BL/6J-background Thy1-EGFP mice were CIE-exposed during adolescence or adulthood and examined, as adults, for alterations in the density and morphology of dendritic spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 68 publications
5
35
1
Order By: Relevance
“…We first examined the behavioral profile of mice undergoing in vivo neuronal recordings. Replicating previous observations (37)(38)(39), the rate of EtOH lever pressing was significantly suppressed during punishment and probe testing, compared with the unpunished baseline period of the punishment session ( Figure 1B, C). The number of shocks received inversely predicted suppression on probe (i.e., positive correlation between EtOH-SA during punishment and probe [r = .61, p = .003]), showing that the degree of suppression during probe testing was not due to the number of shocks received.…”
Section: Punishment Suppresses Etoh-sasupporting
confidence: 89%
See 1 more Smart Citation
“…We first examined the behavioral profile of mice undergoing in vivo neuronal recordings. Replicating previous observations (37)(38)(39), the rate of EtOH lever pressing was significantly suppressed during punishment and probe testing, compared with the unpunished baseline period of the punishment session ( Figure 1B, C). The number of shocks received inversely predicted suppression on probe (i.e., positive correlation between EtOH-SA during punishment and probe [r = .61, p = .003]), showing that the degree of suppression during probe testing was not due to the number of shocks received.…”
Section: Punishment Suppresses Etoh-sasupporting
confidence: 89%
“…Mice were trained in a Med Associates operant chamber (Med Associates, Inc., Fairfax, VT) to respond on the left of two levers on a continuous schedule of reinforcement to earn sucrose pellets during 40-minute sessions (the right, "inactive" lever had no programed consequences) until the criterion was met ($35 rewards), as previously described (37)(38)(39). The pellet was then substituted with a progression of 10-mL liquid rewards ("sucrose fading"; 10% sucrose, 10% sucrose 1 10% EtOH, 5% sucrose 1 10% EtOH, 10% EtOH).…”
Section: Behavioral Testingmentioning
confidence: 99%
“…For instance, adult male rats exposed to ethanol during adolescence (P30-48, 1, 2, 3 or 4 g/kg ethanol, IP) and challenged with a hypnotic ethanol dose regained their righting reflex more rapidly than did their non-exposed counterparts (Matthews et al, 2008), with these alterations evident only following high exposure doses of ethanol (3 and 4 g/kg). These results were also replicated by the same group (Matthews et al, 2017) and others using mice (Jury et al, 2017). However, similar decreases in LORR duration were evident following adult exposure as well (Jury et al, 2017).…”
Section: Ethanol Sensitivity Following Adolescent Ethanol Exposuresupporting
confidence: 68%
“…Many studies that reported increases in ethanol intake following adolescent ethanol exposure did not include other age groups for comparison. Of the studies that included adolescents and adults, previous exposure to ethanol tended to increased ethanol intake later in life regardless of exposure timing (Hefner and Holmes, 2007;Tambour et al, 2008;Strong et al, 2010;Carrara-Nascimento et al, 2013;O'Tousa et al, 2013;Amodeo et al, 2017) or following adult exposure only (Fullgrabe et al, 2007;Jury et al, 2017), suggesting that exposure-related increases in ethanol consumption may not be specific to adolescent exposure. Therefore, it is still not clear whether adolescents are more vulnerable than adults to ethanol-exposure-related increases in ethanol intake.…”
Section: Adolescent Ethanol Exposure: Impact On Ethanol Intake In Adumentioning
confidence: 99%
“…NADIA studies have found AIE alters adult dendritic spine density and shifts spine subtypes in multiple brain regions (Mulholland et al., ; Risher et al., ; Trantham‐Davidson et al., ), a finding that has recently been extended to mice (Jury et al., ). Dendritic spine changes are brain region–specific; for example, in the central and medial, but not basolateral amygdala, AIE exposure reduces total dendritic spine density (Jury et al., ; Pandey et al., ), whereas in medial PFC, AIE increases spine density (Trantham‐Davidson et al., ). The functional status of decreased dendritic spines in the amygdala in adulthood after AIE is not known.…”
Section: Aie‐induced Changes In Adult Brain Cell and Neuroanatomymentioning
confidence: 99%